CALCIFICATION RATE INFLUENCE ON TRACE ELEMENT CONCENTRATIONS IN ARAGONITIC BIVALVE SHELLS: EVIDENCES AND MECHANISMS - Carre M.; Bentaleb I.; Bruguier O.; Ordinola E.; Barrett N.T.; Fontugne M. (My University, 2006)
Trace elements in calcareous organisms have been widely used for paleoclimatic studies. However, the factors controlling their incorporation into mollusc shells are still unclear. We studied here the Sr, Mg, Ba and Mn serial records in the shells of two aragonitic marine bivalve species: Mesodesma donacium and Chione subrugosa from the Peruvian Coast. The elemental concentrations were compared to local temperature and salinity records. The relationships with crystal growth rate G were investigated thanks to well defined periodic growth structures providing a precise shell chronology. Our results show that for both species, environmental parameters only have minor influence, whereas crystal growth rate strongly influences trace elements concentrations, especially for Sr (explaining up to 74% of the variance). The relationship between G and Sr/Ca exhibits variability among the shells as well as inside the shells. For a same growth rate value, Sr/Ca values are higher in more curved shell sections, and the growth rate influence is stronger as well. We show that intercellular and Ca2+-pump pathways cannot support the calcification Ca2+ flux, leading us to propose an alternative mechanism for ionic transport through the calcifying mantle, implying a major role for calcium channels on mantle epithelial cell membranes. In this new calcification model, Sr/Ca shell ratios is determined by Ca2+-channel selectivity against Sr2+, which depends (i) on the electrochemical potential imposed by the crystallisation process and (ii) on the Ca2+-channel density per surface unit on mantle epithelia. ? 2006 Elsevier Inc. All rights reserved.
Keywords: BIVALVE; CALCIFICATION; CRYSTALLIZATION; GEOCHRONOLOGY; SHELL; TRACE ELEMENT; BIVALVIA; CHIONE SUBRUGOSA; MESODESMA DONACIUM; MOLLUSCA